Study of obstacles to the practice of female students at the College of Physical Education and Sports Sciences at Anbar University in the game of football - Mohammed Sadiq Ahmed; Ahmed Jamal Awad; Mustafa Waleed awad; Ahmed Khalid Awad; Othman Abed (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Identify the most important obstacles and difficulties faced by students of the College of Physical Education and Sports Sciences, Anbar University, when playing football, which may contribute to finding appropriate solutions to overcome these obstacles and obstacles and improve the level of the game to increase the base of practice. Objective: This study aims to identify the most important obstacles facing students at the College of Physical Education and Sports Sciences, Anbar University when playing football. Methodology: The descriptive approach was used in the survey method to suit the nature of the study, and the research community consisted of female students of the College of Physical Education and Sports Sciences, Anbar University, for the academic year (2020/2021), numbering (116) students, using the study tool prepared by Walid Munfar, 2010, which identified obstacles to female students' practice of football in four areas, and the triple response scale (Likert) was adopted, after collecting the data, it was statistically processed using the (SPSS) program. Results: After collecting data from the forms distributed to the sample members and analysing them statistically, it was found that (79.61%) of the study sample members have a real desire to play football as a sports activity. Conclusions: There is a positive attitude among students at the College of Physical Education and Sports Sciences at Anbar University towards playing football. The existence of obstacles that prevent students from playing football is represented in the social and family fields, while the artistic and personal fields do not represent an obstacle for them.